Analysis Advantage And Positioning Of My-Nitro: A Study On The Nitrogen Filling Services Industry - Fathur Rohman (International Journal of Economics, Business and Innovation Research, 2023)
This research aims to examine the advantages and positioning of MyNitro PT Widya Inovasi Indonesia (Widya Robotics). With the development of increasingly sophisticated technology and changing people's habits, MyNitro products have been adapted to meet consumer needs. This research uses descriptive quantitative methods and data collection is carried out through observation and analysis assignments during internships. MyNitro has a self-service system and cashless payments as a competitive advantage. Based on the results of Porter's Five Forces analysis, it was found that competition in the MyNitro industry tends to be moderate, this is known from the number of competitors in Indonesia, namely GreenNitrogen which is a competitor of MyNitro.